EdTech for Marginalised Learners in Southeast Asia: Perspectives from funders and providers on priorities, design, investment, and scaling considerations - Jayasinghe, Neema; Chrisani, Aprillia; Honda, Delanie; Gunawan, Clarissa Jazzlyne (EdTech Hub, 2025)
This report presents the findings of a landscape analysis of EdTech interventions designed for the Southeast Asian context. The analysis aims to understand the extent to which EdTech providers and funders in Southeast Asia address the needs of marginalised learners through their priorities in design, investment, and scaling decisions. It focuses on initiatives targeting marginalised groups and those with potential to scale. The research for the study included interviews with funders engaged in the Southeast Asian EdTech space to examine their perspective on EdTech’s impact on marginalised learners, the approaches they adopt to support inclusive solutions, and the drivers behind their investment decisions. This builds on EdTech Hub’s research for the ASEAN-UK SAGE programme, particularly on how EdTech could be used to support improvements in foundational literacy and numeracy, out-of-school children and youth, and learners with disabilities, as well as overcoming gender barriers to employment through the use of EdTech solutions. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Rapport d’Observation du Testing BETA - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo (EdTech Hub, 2025)
This is a report on the Beta testing of a digital learning platform and applications developed for the Ministry of Education in Madagascar. The project aims to train 16,000 teachers, with 2,000 utilising distance learning via tablets. The Beta user testing focused on the pedagogical relevance, usability, and ergonomics of the platform and two offline applications. Twenty-one teachers participated, evaluating tasks like launching applications, navigating content, accessing multimedia, and completing exercises / evaluations. Results showed significant improvement from the Alpha user testing, with high success rates for accessing and navigating modules. However, over 50% of users still found the platform difficult to use, particularly for login, navigation, and profile modification. The applications were generally functional but needed adjustments to content presentation and visual quality. Recommendations included simplifying the platform's interfaces, enhancing user guides, and addressing specific content issues. The document emphasises the importance of ongoing quality assurance and an iterative approach to refining the platform. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce rapport porte sur le test Beta d’une plateforme d’apprentissage numérique et des applications développées pour le Ministère de l’Éducation à Madagascar. Le projet vise à former 16 000 enseignants, dont 2 000 via l’apprentissage à distance sur tablette. Les tests utilisateurs en phase Beta ont évalué la pertinence pédagogique, l’ergonomie et la convivialité de la plateforme ainsi que de deux applications hors ligne. Vingt et un enseignants ont participé, réalisant des tâches telles que le lancement des applications, la navigation dans les contenus, l’accès aux éléments multimédias et la réalisation d’exercices/évaluations. Les résultats montrent une amélioration significative par rapport aux tests Alpha, avec des taux de réussite élevés pour l’accès et la navigation dans les modules. Cependant, plus de 50 % des utilisateurs ont encore rencontré des difficultés, notamment pour la connexion, la navigation et la modification du profil. Les applications étaient globalement fonctionnelles, mais nécessitaient des ajustements dans la présentation des contenus et la qualité visuelle. Les recommandations incluent la simplification des interfaces de la plateforme, l’amélioration des guides utilisateurs et la correction de problèmes spécifiques liés aux contenus. Le document souligne l’importance de l’assurance qualité continue et d’une approche itérative pour affiner la plateforme. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Rapport d’Observation du Testing Alpha - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo; Koomar, Saalim (EdTech Hub, 2025)
This document, details the Alpha user testing of a digital learning platform and educational applications for the Ministry of National Education of Madagascar, aimed at training 2000 teachers. Conducted in July 2024, the testing focused on functionality and accessibility. Twenty-nine testers, primarily web developers and instructional designers, used a Google Forms questionnaire to evaluate the platform and applications. The results showed that while the platform was generally functional, with most features validated, several areas needed adjustments, particularly in accessibility and specific functions like the quiz timer. The applications had more issues, with several features requiring fixes and accessibility being a significant concern. Key recommendations included diagnosing and fixing defective parts, restructuring modules for better accessibility, optimising multimedia file sizes, and creating a detailed user guide. The testing highlighted the need for improvements before the Beta testing phase with teachers. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce document détaille les tests utilisateurs en phase Alpha d’une plateforme d’apprentissage numérique et d’applications éducatives développées pour le Ministère de l’Éducation Nationale de Madagascar, dans le cadre de la formation de 2 000 enseignants. Réalisés en juillet 2024, ces tests ont porté sur la fonctionnalité et l’accessibilité. Vingt-neuf testeurs, principalement des développeurs web et des concepteurs pédagogiques, ont évalué la plateforme et les applications via un questionnaire Google Forms. Les résultats ont montré que, bien que la plateforme soit globalement fonctionnelle avec la plupart des fonctionnalités validées, plusieurs ajustements étaient nécessaires, notamment en matière d’accessibilité et pour certaines fonctions spécifiques comme le minuteur des quiz. Les applications présentaient davantage de problèmes, plusieurs fonctionnalités nécessitant des corrections et l’accessibilité étant un défi majeur. Les principales recommandations incluaient le diagnostic et la correction des éléments défectueux, la restructuration des modules pour une meilleure accessibilité, l’optimisation de la taille des fichiers multimédias et la création d’un guide utilisateur détaillé. Ces tests ont mis en évidence la nécessité d’améliorations avant la phase de test Beta avec les enseignants. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

A Theory of Change for Parents and Caregivers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Ahmed, Shakil; Mazari, Haani; Kaye, Tom; Radford, Kate; Otieno, Jennifer (EdTech Hub, 2022)
The third of a trilogy of Theories of Change (TOCs) that focuses on parents and caregivers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how parents’ and caregivers’ experiences in diverse programmes and initiatives will enable them to support children to improved educational outcomes, and take advantage of available technology. It offers a tool for programme designers, implementers, and evaluators to think critically about how their initiative(s) will impact parents and caregivers for the longer-term benefits of their children. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; parents and caregivers; parenting; education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Sierra Leone Series: Plan International and the importance of community support for distance teacher professional development programmes - McBurnie, Chris; Saidu, Arthur; Rincon Casado, Eusebio; Shergill, Maggie (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen

Sierra Leone series: Plan International and the importance of community support for distance teacher professional development programmes - Saidu, Arthur; Casado, Eusebio Rincon; Shergill, Maggie; McBurnie, Chris (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week four, we met with Arthur Saidu, Eusebio Rincon Casado and Maggie Shergill from…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen